2020
DOI: 10.1002/jcp.29928
|View full text |Cite
|
Sign up to set email alerts
|

Multiomics data reveals the influences of myasthenia gravis on thymoma and its precision treatment

Abstract: Thymoma is a rare characterized by a unique association with autoimmune diseases, especially myasthenia gravis (MG). However, little is known about the molecular characteristics of MG-associated thymoma individuals. We aim to examine the influences of MG on thymoma by analyzing multiomics data. A total of 105 samples with thymoma was analyzed from TCGA and these samples were divided into subgroups with MG (MGT) or without MG (MGF) according to clinical information. We then characterized the differential gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
7
0
1
Order By: Relevance
“…The GTF2I gene is well known for its association with Williams-Beuren syndrome and supravalvular aortic stenosis ( 28 ). Amazingly, recent large-scale genome-wide association studies have identified close association of the GTF2I gene with various autoimmune diseases, including primary Sjögren syndrome ( 29 ), systemic lupus erythematosus ( 30 ), rheumatoid arthritis ( 31 ), myasthenia gravis ( 32 ), ANCA-associated vasculitis ( 33 ), and neuromyelitis optica spectrum disorder ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The GTF2I gene is well known for its association with Williams-Beuren syndrome and supravalvular aortic stenosis ( 28 ). Amazingly, recent large-scale genome-wide association studies have identified close association of the GTF2I gene with various autoimmune diseases, including primary Sjögren syndrome ( 29 ), systemic lupus erythematosus ( 30 ), rheumatoid arthritis ( 31 ), myasthenia gravis ( 32 ), ANCA-associated vasculitis ( 33 ), and neuromyelitis optica spectrum disorder ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…A Chinese study with a cohort of 105 patients reporting and not MG found that patients suffering MG showed elevated inflammatory responses and metabolic related pathways, whereas those patients with no autoimmune event were presented with mesenchymal characteristics (56). Of note, GTF2I mutations were assessed at significantly higher frequency in patients with no autoimmunity (56).…”
Section: Molecular Features Of Aids and Tetsmentioning
confidence: 99%
“…A Chinese study with a cohort of 105 patients reporting and not MG found that patients suffering MG showed elevated inflammatory responses and metabolic related pathways, whereas those patients with no autoimmune event were presented with mesenchymal characteristics (56). Of note, GTF2I mutations were assessed at significantly higher frequency in patients with no autoimmunity (56). Indeed, GTF2I mutation have been correlated with better survival outcomes (57); thus, we could hypothesize that patients with GTF2I alterations would be good candidates for immunotherapy; however, GTF2I mutations have been detected in type A (82%) and type AB (74%) and rarely in the aggressive subtypes (22,57), such as TC, where recurrent mutations of known cancer genes have been identified including TP53, CYLD, CDKN2A, BAP1 and PBRM1 (22,57).…”
Section: Molecular Features Of Aids and Tetsmentioning
confidence: 99%
See 1 more Smart Citation
“…GTF2I gene mutations occur at significantly higher frequencies in thymoma patients with myasthenia gravis than those without(29).GTF2I proteins are unusual transcriptional regulators that function as both basal and signalinduced transcription factors. Among its related pathways are the BCR signaling pathway and RNA polymerase II transcription initiation and promoter clearance.…”
mentioning
confidence: 99%